The Kaizen philosophy in the aluminium products improvement - Borkowski, Stanislaw; Stasiak-Betlejewska, Renata; Naprstkova, Natasa (Manufacturing Technology Journal, 2011)
Kaizen strategy is the most important Japanese management concept. Supporters of this by all means an interesting management philosophy consider it as a basis for achieving success by the company. The analyzed company X Stainless motivated by others companies market successes decided to deepen the knowledge of the Kaizen philosophy, which resulted in the implementation of this method of management in its ranks. The essence of Kaizen is to change ways of thinking and way of production management. Underlying this theory, there is the gradual but constant improvement of the status quo with the active involvement of every management employee and the rest of the company workers. Kaizen educates employees towards finding ways to better perform their duties. Performance of work is closely connected with the observance of standards and the introduction of small improvements in order to continue its improvement.
Keywords: Kaizen; quality; improvement